2017
DOI: 10.1093/jee/tox071
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition Preference and Larval Performance of Cnaphalocrocis medinalis (Lepidoptera: Pyralidae) on Rice Genotypes

Abstract: Cnaphalocrocis medinalis Guenée is a noxious rice pest during cultivated periods. Cnaphalocrocis medinalis moths lay eggs on leaf surfaces, and larvae longitudinally roll the leaves to hide inside the leaf buds and feed on the upper epidermis and mesophyll tissues. In this study, we evaluated the female oviposition preference and larval performance of C. medinalis on six insect-resistant and six insect-susceptible rice genotypes. Female moth choice and no-choice oviposition preferences were studied. The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Two rice (O. sativa L.) varieties, namely, Qingliu and TN1, were used for this study. Qingliu is a C. medinalis-resistant variety 20 , whereas TN1 is a C. medinalis-susceptible variety 21 . Seeds were first surface sterilized with 2% (v/v) NaOCl for 40 min and further washed in distilled water.…”
Section: Methods Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two rice (O. sativa L.) varieties, namely, Qingliu and TN1, were used for this study. Qingliu is a C. medinalis-resistant variety 20 , whereas TN1 is a C. medinalis-susceptible variety 21 . Seeds were first surface sterilized with 2% (v/v) NaOCl for 40 min and further washed in distilled water.…”
Section: Methods Plant Materialsmentioning
confidence: 99%
“…A recent study differentiated C. medinalis -resistant and C. medinalis -susceptible rice genotypes based on larval performance parameters, such as the percentage of rolled leaves 20 . The Qingliu ( indica ) rice genotype exhibited the lowest percentage of rolled-leaf damage inflicted by C. medinalis , indicating the resistance of this genotype to the pest.…”
Section: Introductionmentioning
confidence: 99%
“…1). Seeds of a C. medinalis -resistant rice variety, Qingliu (Liao and Chen 2017), were obtained from TDARES. Qingliu plants have higher mortality rate and lower growth rate on C. medinalis larvae than TN1 plants (Guo et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies consistently showed that the Qingliu (QL) rice variety is resistant to leaffolder infestation [ 24 26 ]. Qingliu is a local native indica rice variety in Taiwan where its cultivation record can be dated back to the Qing dynasty era around 1742 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%